Improving Students Listening Ability Through Application Of Audio-Visual At Smpn 2 Painan - Nurmalinda Nurmalinda (Fakultas Sastra Universitas Ekasakti, 2017)
In order to learn a lesson well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to